Pemanfaatan Bulu Ayam Dan Komposisi Cangkang Rajungan Untuk Meningkatkan Kualitas Fisik Dan Kimia Kompos - Kusmiadi, R; Khodijah, NS; Akbar, A (Universitas Bangka Belitung, 2014)
Utilization of waste chicken feather and crab shells as compost material is an alternative to reduce the environmental pollution caused by waste. This research is identify and study the effect of the addition of crab shells during composting of chicken feather in improving the physical and chemical quality compost chicken feather. The composition compost consists of 1.75 kg of chicken feathersÂ + 0.15 kg of chicken manure + 0.1 kg bran. Treatmentincludesresearch R0 without the addition of crab shells, R1 0,2 kg, R2 0,4 kg, R3 0.6 kg shell crab. This research used a cluster randomized design (RAK) consisting of 4 treatment, which was repeated 3 and each treatment has 3 samples, 36 samples were obtained observations. Observationsonthe observed variableswere analyzedusing theF test. If there is atreatmentthat have areal effect, it willcontinueto usefurthertestingHonestlySignificant Difference(HSD) with a95% confidence level. Physical parameters include is water conten, temperature, and colour of compost. ParametersÂ chemicalÂ include is N, P, K, Ca, C-Organik, and C/N ratio. The results showedthat theaddition 0.6kg ofcrabshellsonly givethe effectin improving quality pH (7,29%), Ca (6,8%), P (1,16%), N-Total (4,16%). Variablesthat have metquality standardsbySNI19-7030-2004compostisN-total, pH, Ca, C-Organic and Phosphorus.